Confronting the Economic and Financial Challenges of Covid-19 : A Conversation with World Bank Group President David Malpass - Malpass, David (World Bank, Washington, DC, 2020)
World Bank Group President, David Malpass spoke about how the past four weeks the World Bank has begun to implement twelve billion-dollar package that would enable vaccination systems for countries that otherwise wouldn't have access, and that was the goal. He explained the assessment of the countries and their ability to deliver vaccines. He mentioned one of the big challenges for the world is how to create systems where people that are poor can build assets. One of the most valuable assets that people have is education, and the second is an actual job. The World Bank wants to amplify social safety nets around the world to get cash or other kinds of support to the poor. That has been a challenge. The debt crisis has been a challenge because you can identify countries where the World Bank would put in resources but all of that would go to creditors, and none of it to the people. Once the grace period runs out for Bank loans, in reality it is a loan that is not going to be paid, and some of the banking systems will come under pressure from domestic debt. One of the challenges that the G20 faces is how to get broad debt relief to countries that were over-indebted. He plugged for trade facilitation. The most important thing for economic development is to quickly get things across borders.